O treh modelih sodniškega nadzora, razpravljanja in pravosodne legitimnosti - Lasser, Mitchel de S.-O.-L'E. (Revus (Ljubljana), 2006)
This paper excerpts and summarizes Professor Lasser's recently published book comparing the argumentative practices of the European Court of Justice, the French Cour de cassation and the United States Supreme Court. It argues that the Cour de cassation depends primarily on an institutional approach for generating judicial control, debate and legitimacy; that the Supreme Court depends primarily on an argumentative approach; and that the ECJ depends on a conglomerate mode that pastes together facets of the institutional and argumentative approaches. The paper claims that the discursive practices, institutional arrangements and conceptual structures of these three courts are best understood by focusing on a fundamental structural feature that distinguishes between the French and American models of judicial discourse. Stated in the simplest terms, this difference boils down to the fact that the French model bifurcates its argumentation into two distinct discursive spheres (only one of which - the syllogistic French judicial decision - is consistently made public), while the American model integrates its two modes of argument in one and the same public space, namely, in the judicial decision itself. The European Court of Justice maintains the bifurcated French discursive model, but softens it by adopting a systemic, "meta" teleological form of argumentation that it deploys publicly in both its judicial decisions and its AG Opinions.
Keywords: Evropska unija; Francija; pravosodje; pravosodni sistemi; primerjalno pravo; sodišča; ZDA